A cross-sectional study on Saudi pharmacists working as medical representatives: What attracted them and what is keeping them in this sector—Misconceptions and reality - Almaghaslah, Dalia; Alsayari, Abdulrhman (Frontiers in Public Health, 2023)
Background: The government in Saudi Arabia issued a labour reform initiative to renationalise the pharmacy profession in pharmaceutical companies to generate more employment for young Saudi pharmacists. Considering the nationalisation of the pharmacy workforce employed in this sector, as well as the younger pharmacists' preferences towards working in this setting, the current study was conducted determine the reasons to choose this career pathway, to clarify the common misconceptions about this sector and to assess job satisfaction, work commitment, and intentions to leave. Methods: An online self-administered questionnaire was used to collect data from pharmacists working as medical representatives across Saudi Arabia. A total of 133 medical representatives participated in the study. Results: The main factors that motivated study participants to join this sector included performing a socially important job, receiving a high salary, and further career development. The common misconceptions about the sector, such as lacking honor and value and considering commercial values to be accepted, were found to be incorrect by the medical representatives. A high job satisfaction level, high work commitment, and low intentions to leave the sector were reported by participants. Conclusion: Working as a medical representative in a pharmaceutical company is an appealing career choice that fulfills young pharmacists' career ambitions and may help in creating more jobs for the increasing numbers of pharmacy graduates.